Ethanol induced jasmonate pathway promotes astaxanthin hyperaccumulation in Haematococcus pluvialis. (October 2019) - Liu, Yu-Hong; Alimujiang, Adili; Wang, Xiang; Luo, Shan-Wei; Balamurugan, Srinivasan; Yang, Wei-Dong; Liu, Jie-Sheng; Zhang, Lin; Li, Hong-Ye
Graphical abstract: Highlights: Ethanol (0.4%) remarkably increased algal astaxanthin content. Astaxanthin monoester was found to be the predominant compound. Ethanol altered structural and biochemical properties of the cell. Ethanol orchestrated methyl jasmonate pathway thereby enhanced astaxanthin. Abstract: Haematococcus pluvialis is a main biological resource for the antioxidant astaxanthin production, however, potential modulators and molecular mechanisms underpinning astaxanthin accumulation remain largely obscured. We discovered that provision of ethanol (0.4%) significantly triggered the cellular astaxanthin content up to 3.85% on the 4th day of treatment. Amongst, 95% of the accumulated astaxanthin was esterified, particularly enriched with monoesters. Ultrastructural analysis revealed that ethanol altered cell wall structure and physiological properties. Antioxidant analyses revealed that astaxanthin accumulation offset the ethanol induced oxidative stress. Ethanol treatment reduced carbohydrates while increased lipids and jasmonic acid production. Transcriptomic analysis uncovered that ethanol orchestrated the expression of crucial genes involved in carotenogenesis, e.g. PSY, BKT and CRTR-b were significantly upregulated. Moreover, methyl jasmonic acid synthesis was induced and played a major role in regulating the carotenogenic genes. The findings uncovered the novel viewpoint in the intricate transcriptional regulatory mechanisms of astaxanthin biosynthesis.